A Challenging Yet Motivating Journey: The Experiences of Young Adult Parents With Serious Mental Health Conditions in the USA - Sabella, Kathryn; Baczko, Amanda; Lane, Ian A.; Golden, Laura; Pici-D'Ottavio, Emma; O'Neill, Murron (Frontiers in Psychiatry, 2022)
In recent decades the average age of becoming a parent has increased, the rate of teen pregnancies has decreased, and a new developmental period of emerging adulthood is marked by diverse pathways into adulthood. Today, those who become parents in young adulthood (18–24 years old) and their children may be vulnerable to poor outcomes observed in teen parents (13–19 years old) of previous generations. Young adults with serious mental health conditions (SMHC) who encounter additional challenges navigating young adulthood and tend to parent earlier than their peers may be at particularly increased risk of poor outcomes. To date, little research has been done to understand the experiences of young adult parents, especially those with SMHC. This study describes themes from qualitative interviews with 18 young adults with SMHC in the United States who became parents before the age of 25. Life story narrative interviews, conducted mostly by young adults with lived experience, asked participants to describe their parenting and mental health experiences and their school, training, and work experiences. Participants described the challenges of simultaneously parenting young children and managing a mental health condition, experiences of discrimination, and fear of future discrimination related to their mental health condition. However, parents also expressed that their children motivated them to maintain recovery and build a good life for their family. This is the first study to qualitatively explore the experiences of young adult parents with SMHC. While many of these findings align with prior qualitative research on mothers with mental illness, by exclusively focusing on individuals who become parents earlier than their peers and including father experiences, this research adds to our understanding of how individuals simultaneously navigate parenting and managing a serious mental health condition. These findings should inform larger-scale research studies on the experiences and outcomes of young adults with SMHC who become parents in their late teens or early twenties. A better understanding of their experiences should inform public mental health services that incorporate parenting as an important element of an individual's personal recovery model.